2022
DOI: 10.3390/en15051897
|View full text |Cite
|
Sign up to set email alerts
|

Methods of Handling the Cup Plant (Silphium perfoliatum L.) for Energy Production

Abstract: The aim of the study was to determine the possibilities of using cup plants (Silphium perfoliatum L.) to generate energy. The energy balances of the combustion and anaerobic digestion were compared. The research showed that cup plants could be used as a raw material for solid fuel and for anaerobic digestion. An energy balance simulation showed that electricity could be generated through the anaerobic digestion of cup plants. The following amounts could be generated in the anaerobic digestion process: 1069 kWh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…At this stage, polymers are converted into soluble monomers by enzymatic hydrolysis. The reaction is catalysed by extracellular enzymes of microorganisms called hydrolases or lyases [80]. However, not all substances, especially those that belong to the so-called lignocellulosic biomass, yield to hydrolytic enzymes with equal ease.…”
Section: Pretreatmentsmentioning
confidence: 99%
“…At this stage, polymers are converted into soluble monomers by enzymatic hydrolysis. The reaction is catalysed by extracellular enzymes of microorganisms called hydrolases or lyases [80]. However, not all substances, especially those that belong to the so-called lignocellulosic biomass, yield to hydrolytic enzymes with equal ease.…”
Section: Pretreatmentsmentioning
confidence: 99%
“…Kanadchanka, S. scaberrinum Ell., S. trifoliatum L.) from Ukraine was from 29.46% (S. integrifolium) to 48.24% (S. lacinatum). Witaszek et al [105] showed that the content of lignocellulosic compounds in the dry matter of the aboveground parts of S. perfoliatum was 21.62% lignin, 30.96% cellulose, and 22.6% hemicellulose.…”
Section: Carbohydratesmentioning
confidence: 99%
“…Sustainable biomass is an important fuel for mitigating climate change and decarbonizing the energy sector. Due to the high content of lignocellulosic fibers (cellulose, hemicellulose, and lignin) in the biomass of S. perfoliatum (about 90% dry weight), pre-treatment (extrusion or comminution) is necessary to increase biodegradability during anaerobic fermentation [105]. Research conducted in Poland has shown that S. perfoliatum can be used as a raw material for solid fuel and for anaerobic digestion.…”
Section: Application As An Energy Cropmentioning
confidence: 99%
See 1 more Smart Citation
“…Lesser-known plants with the prospect of being used not only for energy purposes include the cup plant Silphium perfoliatum L, a promising novel crop that is still not widely distributed (Marišová et al, 2016;Cumplido-Marin et al, 2020;Hauptvogel et al, 2022;Reinhardt et al, 2022). The indisputable advantage of the cup plant is the suitability of the phytomass for various uses, while most of recent research works are focused on potential in biogas production (Siwek et al, 2019;Guo et al, 2020;Kowalska et al, 2020;von Cossel et al, 2020;Witaszek et al, 2022) and there is little knowledge and information enabling reliable cultivation technology (Shittenhelm et al, 2021;Hryniewicz et al, 2021;Tsugkiev et al, 2021;MarieEnde at al., 2021). Even the forms of usability themselves are not yet sufficiently parameterized and it concerns further energy and feed purposes, pharmaceutical uses or honey production, and the protection of animals and their living space is also worth mentioning.…”
Section: Introductionmentioning
confidence: 99%